Temperature-dependent oviposition and nymph performance reveal distinct thermal niches of coexisting planthoppers with similar thresholds for development - Horgan, Finbarr G.; Arida, Arriza; Ardestani, Goli; Almazan, Maria Liberty P. (Public Library of Science, 2020)
The brown planthopper (Nilapavata lugens: BPH) and whitebacked planthopper (Sogatella furcifera: WBPH) co-occur as the principal pests of rice in Asia. A review of previous studies suggests that the two species have similar temperature tolerances and similar temperature thresholds for development. However, the distribution and seasonality of WBPH suggest that its temperature optima for performance (survival, oviposition and growth) may be lower than for BPH. We compared adult longevity, oviposition, nymph survival and development success, as well as nymph biomass in both species across a gradient of constant temperatures from 15°C-40°C, at 5°C intervals. The most suitable temperatures for oviposition, nymph biomass and development success were 5–10°C lower for WBPH than for BPH. Furthermore, compared to BPH, WBPH demonstrated clear differences in oviposition on different rice subspecies and on rice at different growth stages at 25°C and 30°C, but not at other temperatures. The results suggest that aspects of herbivore performance within tolerable temperature ranges, which are not often included in temperature models, may be more useful than thermal tolerances or development thresholds in predicting the effects of global warming on pest damage to crops.